1998
DOI: 10.1038/sj.ijo.0800655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet, physical activity and parents’ obesity on children’s adiposity: a four-year longitudinal study

Abstract: The parents' obesity was the main risk factor for obesity in this group of children. Sedentary behaviour (TV viewing) was independently associated with overweight at the age of 8 y. Physical activity and energy and nutrient intakes did not significantly affect the change in rel BMI over the four-year period when the parents' obesity was taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
179
5
21

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(228 citation statements)
references
References 18 publications
(26 reference statements)
23
179
5
21
Order By: Relevance
“…This result is consistent with a growing body of evidence that, among children and adolescents, inactivity (particularly watching TV) is associated with body fatness in cross-sectional (Andersen et al, 1998;Hernandez et al, 1999;Tremblay and Willms, 2003), longitudinal (Maffeis et al, 1998;Berkey et al, 2000) and intervention studies Robinson, 1999). Obesity in children has even been reported to correlate in a dosedependent manner with baseline daily duration of television viewing in longitudinal observations (Dietz and Gortmaker, 1985;Gortmaker et al, 1996), suggesting a cause-effect relationship.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is consistent with a growing body of evidence that, among children and adolescents, inactivity (particularly watching TV) is associated with body fatness in cross-sectional (Andersen et al, 1998;Hernandez et al, 1999;Tremblay and Willms, 2003), longitudinal (Maffeis et al, 1998;Berkey et al, 2000) and intervention studies Robinson, 1999). Obesity in children has even been reported to correlate in a dosedependent manner with baseline daily duration of television viewing in longitudinal observations (Dietz and Gortmaker, 1985;Gortmaker et al, 1996), suggesting a cause-effect relationship.…”
Section: Discussionsupporting
confidence: 86%
“…The absence of a significant relationship between physical activity and OW found in the preadolescent and adolescent groups is only partially shared in the literature. Crosssectional and longitudinal studies are roughly divided between finding no effect (McMurray et al, 1995;Goran et al, 1997;Maffeis et al, 1998;Kimm et al, 2001), or a protective effect of activity (Moore et al, 1995;Hernandez et al, 1999;Berkey et al, 2000;O'Loughlin et al, 2000;Tremblay and Willms, 2003;Janssen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…76 Low levels of physical activity and greater amounts of sedentary pursuits, in particular television viewing (43 h/ days), during childhood and/or adolescence is predictive of greater future adiposity and or overweight. [77][78][79][80][81][82][83][84] Thus, the rationale for prescribing exercise as an adjunct to dietary restriction is compelling given its potential to reduce overweight-related comorbidity and the hazard associated with dietary restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have investigated the influence of lifestyle determinants on childhood overweight (e.g. lifestyle factors (3)(4)(5)(6)(7)(8)(9) ), but only few studies have addressed familial, social and lifestyle factors together (10)(11)(12)(13)(14)(15)(16)(17) . In these cross-sectional studies, parental obesity, low socio-economic status (SES), high weight gain during infancy and television (TV) viewing were found as main determinants of prevalence.…”
mentioning
confidence: 99%
“…In these cross-sectional studies, parental obesity, low socio-economic status (SES), high weight gain during infancy and television (TV) viewing were found as main determinants of prevalence. Contrary to cross-sectional data, there are only very few longitudinal studies investigating the development of overweight (14,(18)(19)(20)(21) . In these studies parental overweight was found as the main determinant.…”
mentioning
confidence: 99%